Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan pada Perusahan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Nashrullah, Zulkornain; Rizki, Rizki; Dewi, Ratna Kusuma (JYRS: Journal of Youth Research and Studies, 2024)
This study aims to determine the effect of financial performance on company value. Financial performance is measured by the Liquidity (CR), Profitability (ROE), and Solvency (DER) ratios. The objects studied in this study are food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2022 period. This study is a quantitative study with a population of 84 companies from the food and beverage sub-sector listed on the IDX. Based on the specified criteria, a sample of 8 food and beverage sub-sector companies was obtained using purposive sampling techniques. This study uses descriptive statistical analysis methods, panel data regression, classical assumption tests, and hypothesis tests processed using Eviews 13. The results of the study indicate that partially Current Ratio (CR) has no effect on company value, Return On Equity (ROE) has a positive and significant effect on company value and Debt to Equity Ratio (DER) has a negative and significant effect on value. Meanwhile, simultaneously Current Ratio (CR), Return On Equity (ROE), and Debt to Equity Ratio (DER) have a significant effect on company value with an F-statistic of 0.000751 <0.05.